Human RecQ Helicases in DNA Double-Strand Break Repair - Lu, Huiming; Davis, Anthony J. (Frontiers in Cell and Developmental Biology, 2021)
RecQ DNA helicases are a conserved protein family that are found in bacteria, fungus, plants, and animals. These helicases play important roles in multiple cellular functions, including DNA replication, transcription, DNA repair, and telomere maintenance. Humans have five RecQ helicases, RECQL1, BLM, WRN, RECQL4, and RECQL5. Defects in BLM and WRN cause the autosomal disorders, Bloom syndrome (BS) and Werner syndrome (WS), respectively. Mutations in RECQL4 are associated with three genetic disorders, Rothmund-Thomson syndrome (RTS), Baller-Gerold syndrome (BGS), and RAPADILINO syndrome. Although no genetic disorders have been reported due to loss of RECQL1 or RECQL5, dysfunction of either gene is associated with tumorigenesis. Multiple genetically independent pathways have evolved that mediate the repair of DNA double-strand break (DSB) and RecQ helicases play pivotal roles in each of them. The importance of DSB repair is supported by the observations that defective DSB repair can cause chromosomal aberrations, genomic instability, senescence, or cell death, which ultimately can lead to premature aging, neurodegeneration, or tumorigenesis. In this review, we will introduce the human RecQ helicase family, describe in detail their roles in DSB repair, and provide relevance between the dysfunction of RecQ helicases and human diseases.